Metodologia para a quantificação da exalação do gás radônio em rochas ornamentais - Artur, Antonio Carlos [UNESP]; Bonotto, Daniel Marcos [UNESP]; Do Amaral, Paulo Giovany Quadros [UNESP]; Galembeck, Tamar Milca Bortolozzo [UNESP] (My University, 2013)
A method for quantifying radon gas exhalation from dimension stones. This work describes a method for quantifying the radon gas exhaled from dimension stones that was settled in DPM/IGCE/UNESP/Rio Claro. The radon gas is radioactive, being considered cancerigenous, reinforcing the need for realizing studies focusing its presence in the environment. Some methods for quantifying the radon exhaled from rocks are complicated, requesting several laboratorial steps for data acquisition, what implies on the gas loss according to the time increase for obtaining the results. The technique utilized is easy for data acquisition that is obtained by measurement cycles. The main challenge consisted on the sample sealing for analysis in a vessel maintaining certain internal vacuum pressure by a relatively long time period, equivalent to 25 days needed for 222Rn to reach secular radioactive equilibrium and that permitted its coupling to the device measuring gas without interference of the external air. The procedures allowed realize the radon monitoring and quantification in several dimension stones, contributing to the development of the researches about the behavior and diffusion of this gas in stony materials.
Methodology for measurement of exhalation of radon gas in stones
Keywords: Dimension stone; Radioactivity; Radon gas exhalation; Silicate rocks